DEEP LEARNING MODEL OF MASKING VISION BASED AUTONOMOUS NAVIGATION FOR DRONES - LEE WAI, ALVIN CHUNG (2019)
Widely known as drone, an unmanned aerial vehicle (UAV), has been around for years and still gaining massive attention as a way of boosting the growth of artificial intelligence applications. The recent technological advancements have made significant breakthroughs in the area of deep learning, computer vision and UAV, which consequently expanding drone applications beyond the battlefield. This can be seen in the recent roles of drone to perform complex tasks such as environmental and natural disaster monitoring, border surveillance, emergency assistance, search and rescue missions and relay communications. Autonomous drone navigation becomes challenging due to the unstable and weak GPS signals coverage.